Open Knowledge Pada Gerakan Free Culture Sebagai Preservasi Budaya di Media Siber - Suherman, Anggung (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2019)
This research aims to reveal and analyze the movement of free culture on the website Aural Archipelago as audio library which preserve the culture through archiving. The emergence of free culture in the provision of data and information through archiving provides an opportunity for the public to be able to access unlimited various information legally. The collection in Aural Archipelago is a digital audio library that focuses on traditional music. Its completeness and freedom of access is better than the Indonesian government departments assigned to related issues. The research method uses qualitative with Cyber Media analysis approach, exploring how free culture becomes a movement in a new media preserving culture through archiving. The theory applied is the combination theory of Cyber Media by Rulli Nasrullah with the Virtual Ethnography by Christine Hine who thoroughly examines the world of reality with the world of cyber. Aural Archipelago provides information data generated through ethnographic processes. The expedition and its documentation are archived through the digital library model and has granted permission for the user to redistribute the archives to others. The result of open knowledge including new works to be the subject of research, academic needs, innovation, inspiration and collaboration.Keywords: Free Culture, Open Knowledge, Cultural Preservation, Digital Library